Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Quantifying Virtual Field Trip Efficiency - J. H. Pugsley; J. A. Howell; A. J. Hartley; S. J. Buckley; M. Chmielewska; N. Naumann; N. J. Schofield; R. Brackenridge (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2024)
The efficiency of virtual field trips (VFTs) compared to their physical counterparts, is often regarded as one of their key benefits. Virtual field trips are typically more time, cost and environmentally efficient and logistically easier to plan and execute. This is largely due to the lack of travel, however, the nature of these efficiencies, which is essential for deciding whether a trip should be virtual, physical or blended, have not previously been quantified. Here we present a quantitative evaluation of several measures of efficiency, using data from a like-for-like comparison between 10 day long virtual and physical field trips to Utah, USA, from the University of Aberdeen, UK. For this case study, our results demonstrate that virtual field trips are more efficient across all the categories of time, cost, environmental impact, and logistics. In addition to saved air travel days at the start and end of the physical trip, a further 33.3% of the time on the physical field trip was spent travelling (walking and driving). This time saving allowed an additional 16 localities to be visited on the virtual field trip. The virtual field trip localities also ran in an order that best suited the geological narrative rather than their geographic location which the physical field trip was restricted by. Flights and driven kilometres for the physical trip produced c. 4 t of carbon dioxide equivalent (CO 2 ) per student. The virtual trip produce <1% of the CO 2 and was comparable to a typical teaching week, making it significantly more environmentally efficient. The cost of the virtual trip was negligible compared to that of the physical trip (saving up to £ 3000 GBP per student). These findings were compared to the fulfilment of learning outcomes, quantified primarily through questionnaires, the student responses suggest that the PFT and VFT perceptions of learning outcomes were generally comparable. Efficiency is not the only measure of a successful field trip, with other parameters such as social cohesion and embodiment within the outdoor environment that must also be considered when planning a field trip. Therefore, the authors do not advocate or support an abandonment of physical field trips. Rather, this study aims to provide a first attempt to quantify efficiency to inform decision making when planning field training.

Synthesizing the spatial functionality of contemporary stock assessment software to identify future needs for next generation assessment platforms - Aaron M. Berger; Caren Barceló; Daniel R. Goethel; Simon D. Hoyle; Patrick D. Lynch; Jeremy McKenzie; Alistair Dunn; André E. Punt; Richard D. Methot; John Hampton; Clay E. Porch; Richard McGarvey; et al. (Fisheries Research, 2024)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

A Blueprint for an Inclusive, Global Deep-Sea Ocean Decade Field Program - Kerry L. Howell; Ana Hilário; A. Louise Allcock; David M. Bailey; Maria Baker; Malcolm R. Clark; Ana Colaço; Jon Copley; Erik E. Cordes; Roberto Danovaro; Awantha Dissanayake; Elva Escobar; et al. (Frontiers in Marine Science, 2020)
The ocean plays a crucial role in the functioning of the Earth System and in the provision of vital goods and services. The United Nations (UN) declared 2021–2030 as the UN Decade of Ocean Science for Sustainable Development. The Roadmap for the Ocean Decade aims to achieve six critical societal outcomes (SOs) by 2030, through the pursuit of four objectives (Os). It specifically recognizes the scarcity of biological data for deep-sea biomes, and challenges the global scientific community to conduct research to advance understanding of deep-sea ecosystems to inform sustainable management. In this paper, we map four key scientific questions identified by the academic community to the Ocean Decade SOs: (i) What is the diversity of life in the deep ocean? (ii) How are populations and habitats connected? (iii) What is the role of living organisms in ecosystem function and service provision? and (iv) How do species, communities, and ecosystems respond to disturbance? We then consider the design of a global-scale program to address these questions by reviewing key drivers of ecological pattern and process. We recommend using the following criteria to stratify a global survey design: biogeographic region, depth, horizontal distance, substrate type, high and low climate hazard, fished/unfished, near/far from sources of pollution, licensed/protected from industry activities. We consider both spatial and temporal surveys, and emphasize new biological data collection that prioritizes southern and polar latitudes, deeper (> 2000 m) depths, and midwater environments. We provide guidance on observational, experimental, and monitoring needs for different benthic and pelagic ecosystems. We then review recent efforts to standardize biological data and specimen collection and archiving, making “sampling design to knowledge application” recommendations in the context of a new global program. We also review and comment on needs, and recommend actions, to develop capacity in deep-sea research; and the role of inclusivity - from accessing indigenous and local knowledge to the sharing of technologies - as part of such a global program. We discuss the concept of a new global deep-sea biological research program ‘ Challenger 150 ,’ highlighting what it could deliver for the Ocean Decade and UN Sustainable Development Goal 14.

Effects of early life stress on cocaine self-administration in post-pubertal male and female rhesus macaques - Alison G. P. Wakeford; Elyse L. Morin; Sara N. Bramlett; Brittany R. Howell; Kai M. McCormack; Jerrold S. Meyer; Michael A. Nader; Mar M. Sanchez; Leonard L. Howell (Psychopharmacology, 2019)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Platelet development in cuboid diamonds: insights from micro-FTIR mapping - D. Howell; C. J. O’Neill; K. J. Grant; W. L. Griffin; S. Y. O’Reilly; N. J. Pearson; R. A. Stern; T. Stachel (Contributions to Mineralogy and Petrology, 2012)

Oxidation promotes insertion of the CLIC1 chloride intracellular channel into the membrane - Sophia C. Goodchild; Michael W. Howell; Nicole M. Cordina; Dene R. Littler; Samuel N. Breit; Paul M. G. Curmi; Louise Jennifer Brown (European Biophysics Journal, 2009)

Artificial dietary regime may impair subsequent foraging behaviour of hatchery‐reared turbot released into the natural environment - T. Ellis; R. N. Hughes; B. R. Howell (Journal of Fish Biology, 2002)
When offered a size range of shrimp Crangon crangon , fewer naïve reared turbot Scophthalmus maximus fed than did wild fish, and those that fed took smaller prey. Analysis of feeding behaviour indicated differences between wild and naïve reared fish in the motivation to feed on novel prey and in prey recognition and capture efficiency. Feeding efficiency and motivation increased with experience and reared fish achieved the feeding rate of wild fish within the 9 days of the experiment. The ‘creep’ style of approach to shrimp was innate to naïve reared turbot. A comparative feeding experiment confirmed that experienced reared fish ate more prey than naïve reared fish. Naïve reared turbot selected pellets and attacked stones preferentially to shrimp, in contrast to wild and experienced reared fish, which selected shrimp. Stones were attacked due to the memory of pellet‐like visual characteristics and this behaviour persisted in some reared fish for at least 6 weeks, illustrating a cost of memory in which changing environmental conditions cause previously learnt information to become misleading. The experimental data also demonstrated that differences may arise in the prey and feeding behaviour of wild and naïve reared fish, but that such differences diminish with experience.

A suite of highly polymorphic microsatellite markers in turbot ( Scophthalmus maximus L.) with potential for use across several flatfish species - A. Iyengar; S. Piyapattanakorn; D. A. Heipel; D. M. Stone; B. R. Howell; A. R. Child; N. Maclean (Molecular Ecology, 2000)